Fitting the mixed Rasch model to a reading comprehension test: Exploring individual difference profiles in L2 reading. (October 2016) - Aryadoust, Vahid; Zhang, Limei
The present study used the mixed Rasch model (MRM) to identify subgroups of readers within a sample of students taking an EFL reading comprehension test. Six hundred and two (602) Chinese college students took a reading test and a lexico-grammatical knowledge test and completed a Metacognitive and Cognitive Strategy Use Questionnaire (MCSUQ) (Zhang, Goh, & Kunnan, 2014). MRM analysis revealed two latent classes. Class 1 was more likely to score highly on reading in-depth (RID) items. Students in this class had significantly higher general English proficiency, better lexico-grammatical knowledge, and reported using reading strategies more frequently, especially planning, monitoring, and integrating strategies. In contrast, Class 2 was more likely to score highly on skimming and scanning (SKSN) items, but had relatively lower mean scores for lexico-grammatical knowledge and general English proficiency; they also reported using strategies less frequently than did Class 1. The implications of these findings and further research are discussed.